Women's Empowerment in Rural Community-Driven Development Projects - Independent Evaluation Group (World Bank, Washington, DC, 2017)
Community-driven development (CDD) interventions rest on the principle of empowering communities. Yet, the gender-specific impacts of CDD, especially on empowerment, have not received due attention in evaluation and, more generally, in the theoretical and empirical literature. This report explores evidence of how the CDD approach can create and enhance participation and decision making when women, as well as men, are to be included in the “community” voice and choice. It reviews the theoretical and empirical literature and analyzes World Bank–supported CDD projects. Its intent is to help practitioners who implement CDD interventions more explicitly define, discuss, and integrate gender-relevant elements in the design of CDD projects; be more effective in implementing and monitoring features that may affect men and women differently; and identify meaningful indicators and information to assess gender impacts. Findings of this report include: i) it is important to bring it out empowerment explicitly in the results chain of the project; ii) the design of CDD projects could benefit from being informed by gender-specific needs assessments to identify the constraints that women face in the rural space; iii) It is useful to think of empowerment along the three categories of economic, political, and social empowerment to identify the mechanisms CDD interventions can leverage, and to identify direct and indirect effects; iv) the importance of defining in CDD projects which dimensions can be affected, through which channels, and how these effects can be measured; v) participation needs to be measured in a comprehensive way by the use of multiple indicators; vi) CDD interventions should better frame what they can impact both in the short and the long term, and vii) the learning potential of what works to increase women’s empowerment can be improved through more systematic assessment, reporting and evaluation.